A Classical Geometric Relationship That Reveals The Golden Link in Nature - K. Rajput, Chetansing (JOURNAL OF ADVANCES IN MATHEMATICS, 2019)
This paper introduces the perfect complementary relationship between the 3-4-5 Pythagorean triangle and the 1:2: right-angled triangle. The classical geometric intimacy between these two right triangles not only provides for the ultimate geometric substantiation of Golden Ratio, but it also reveals the fundamental Pi: Phi correlation (π: φ), with an extreme level of precision, and which is firmly based upon the classical geometric principles.